2009
DOI: 10.1080/10611860902963039
|View full text |Cite
|
Sign up to set email alerts
|

Proniosomal transdermal therapeutic system of losartan potassium: development and pharmacokinetic evaluation

Abstract: The purpose of the current study was to investigate the feasibility of proniosomes as transdermal drug delivery system for losartan potassium. Different preparations of proniosomes were fabricated using different nonionic surfactants, such as Span 20, Span 40, Span 60, Span 80, Tween 20, Tween 40, and Tween 80. Different formulae were prepared and coded as PNG-1 (proniosomal gel-1) to PNG-7. The best in vitro skin permeation profile was obtained with proniosomal formulation PNG-2 in 24 h. The permeability para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 10 publications
0
32
0
Order By: Relevance
“…Ibuprofen (Hu & Rhodes, 1999) Proniosomes (prolonged release for improved anti-inflammatory activity) NSAID 11 Losartan potassium (Thakur et al, 2009 easy storage and handling, increased stability. Encapsulation of drug in niosomal formulations reduces the toxicity in various therapies and applications and also prolongs the encapsulated drug circulation time and changes drug distribution in the body (Azmin et al, 1985;Baillie et al, 1985;Ruckmani et al, 2002).…”
Section: Proniosomes As Drug Carriersmentioning
confidence: 99%
“…Ibuprofen (Hu & Rhodes, 1999) Proniosomes (prolonged release for improved anti-inflammatory activity) NSAID 11 Losartan potassium (Thakur et al, 2009 easy storage and handling, increased stability. Encapsulation of drug in niosomal formulations reduces the toxicity in various therapies and applications and also prolongs the encapsulated drug circulation time and changes drug distribution in the body (Azmin et al, 1985;Baillie et al, 1985;Ruckmani et al, 2002).…”
Section: Proniosomes As Drug Carriersmentioning
confidence: 99%
“…LP proniosomes were formulated by method reported by Thakur et al 6 . Optical microscopy photographs confirmed the successful fabrication of LP proniosomes.…”
Section: Resultsmentioning
confidence: 99%
“…Formulation of LP proniosomes: LP proniosomes formulated in present study were reported in literature by Thakur et al 6 . Briefly, proniosomes were prepared by mixing the drug with weighed quantities of non-ionic surfactant (Span-60), L-α-lecithin from egg yolk and cholesterol in a wide mouth glass tube ( Table 1).…”
Section: Materials and Methods: Losartanmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, group 4 which treated transdermally with GM loaded proniosomal gel, showed slow hypoglycemic effect and the maximum reduction in the BGL appeared after 6 h (Tmax). The hypoglycemic activity was extended to 24 h by transdermal administration of proniosomal gel loaded with GM compared with the oral administration of GM suspension which terminated after 6 h. 27 Proniosomal GM gel application resulted in 65.34 ± 6.54% (101.68 ± 15.88 mg/dl, reduction in BGL) after 6 h while the inhibition in the BGL produced by the application of GM loaded HPMC gel was 31.71 ± 5.15% after 6 h. The obtained hypoglycemic activity difference between GM loaded proniosomal gel and GM loaded HPMC gel was around two folds. The results confirm the fact that a significant amount of GM was delivered from the proniosomal gel through rat skin to induce the hypoglycemic effect, so it was concluded that proniosomes enhanced drug delivery through the skin, thereby enhance the pharmacological effect.…”
Section: Hypoglycemic Activity Studymentioning
confidence: 99%